The cult of Santiago Apóstol in Mexico and Peru, revealing of an inculturated Christianity - Cardaillac, Louis (2004)
Historian Georges Baudot writes: "The spiritual conquest of America is possibly the greatest enterprise of ideological transmutation of modern times." Among those values ​​that passed from one continent to another was the cult of saints.